Local Government Efforts in Control of Inflation in Papua's Highlands Province - Syamsul Bahri Abd. Rasyid; Ilham Ilham; Misran Misran (Magister Ilmu Administrasi Publik, 2025)
This research describes the efforts of the Papua’s Highlands Province government in controlling inflation, including policy implications and recommendations that may serve as a reference for future governance. A Qualitative research method was employed using the Miles–Huberman analysis model, supported by NVivo 12 Plus for qualitative coding and VOSviewer for bibliometric analysis. The findings show that inflation is a priority program for the provincial government. Efforts undertaken include restructuring the Regional Inflation Control Team (TPID), establishing a small secretariat team, strengthening the logistics system, improving the Trans Papua Road segment through a Public–Private Partnership (PPP) scheme—particularly the severely damaged Wamena–Jayapura corridor—and promoting local food sovereignty. Special autonomy authority, flexible policy instruments, and adequate development funding are expected to lay a strong foundation for long-term stability and economic sustainability in Papua’s Highlands Province, including maintaining a stable inflation rate.